Measurement properties of quality‐of‐life outcome measures for children and adults with eczema: A systematic review update 2.0. Issue 3 (27th March 2023) - Gabes, Michaela; Donhauser, Theresa; Piontek, Katharina; Kann, Gesina; Fechtner, Marie; Gulde, Isabell; Knüttel, Helge; Apfelbacher, Christian; ,
Abstract: A systematic review on measurement properties of patient‐reported outcome measures (PROMs) for the assessment of quality of life (QoL) in children and adults with eczema was published in 2016 and updated in 2019. We now aimed to systematically assess the measurement properties of PROMs based on recently published development and validation studies regarding quality‐of‐life skin‐ or disease‐specific PROMs using the COnsensus‐based Standards for the selection of health Measurement Instruments (COSMIN) guidelines and integrate these findings with those from the 2019 update. A systematic literature search was conducted in PubMed and Embase. Eligible studies reported on measurement properties of QoL skin‐ or disease‐specific PROMs for the assessment of QoL in children and adults with eczema. The methodological quality of the included studies was evaluated using the COSMIN Risk of Bias checklist. The methodological quality of the included PROMs was judged using updated criteria for good measurement properties, and the quality of evidence was graded. The new evidence was integrated into the results from the 2019 update. Finally, a recommendation for use of the identified PROMs was derived based on all evidence. We identified 12 studies fulfilling our inclusion criteria. Based on the newly generated evidence, the Childhood Atopic Dermatitis Impact Scale—short form (CADIS‐SF) for infants and the Skindex for adults can be recommended for use. We identified three new PROMs, which have the potential to be used, but require further validation: the Pediatric Allergic Disease Quality of Life Questionnaire (PADQLQ), the Skindex‐Mini, and the Scratch Intensity and Impact Scale (SIIS). All other assessed PROMs still have the opportunity to be recommended for use (except for the Dermatology Life Quality Index (DLQI)) but need further validation. Currently, two PROMs for the assessment of QoL in eczema can be recommended for use: the CADIS‐SF for infants and the Skindex for adults. Many PROMs, including the recently developed and/or validated PROMs PADQLQ, Skindex‐Mini and SIIS, need further validation.